Dosing regimens of cotrimoxazole (trimethoprim-sulfamethoxazole) for melioidosis. - Cheng, A; McBryde, E; Wuthiekanun, V; Chierakul, W; Amornchai, P; Day, N; White, N; Peacock, S (2009)
Melioidosis is an infectious disease with a propensity for relapse, despite prolonged antibiotic eradication therapy for 12 to 20 weeks. A pharmacokinetic (PK) simulation study was performed to determine the optimal dosing of cotrimoxazole (trimethoprim-sulfamethoxazole [TMP-SMX]) used in current eradication regimens in Thailand and Australia. Data for bioavailability, protein binding, and coefficients of absorption and elimination were taken from published literature. Apparent volumes of distribution were correlated with body mass and were estimated separately for Thai and Australian populations. In vitro experiments demonstrated concentration-dependent killing. In Australia, the currently used eradication regimen (320 [TMP]/1,600 [SMX] mg every 12 h [q12h]) was predicted to achieve the PK-pharmacodynamic (PD) target (an area under the concentration-time curve from 0 to 24 h/MIC ratio of >25 for both TMP and SMX) for strains with the MIC90 of Australian strains (< or = 1/19 mg/liter). In Thailand, the former regimen of 160/800 mg q12h would not be expected to attain the target for strains with an MIC of > or = 1/19 mg/liter, but the recently implemented weight-based regimen (<40 kg [body weight], 160/800 mg q12h; 40 to 60 kg, 240/1,200 mg q12h; >60 kg, 320/1,600 mg q12h) would be expected to achieve adequate concentrations for strains with an MIC of < or = 1/19 mg/liter. The results were sensitive to the variance of the PK parameters. Prospective PK-PD studies of Asian populations are needed to optimize TMP-SMX dosing in melioidosis.